DO CAMPO À MATEMÁTICA: OS PRINCÍPIOS DA MODELAGEM MATEMÁTICA PARA UMA APRENDIZAGEM SIGNIFICATIVA - Vargas, Andressa Franco (2020)
This qualitative research aims to analyze the contribution of Mathematical Modeling to a significant learning of mathematical content, through the inclusion of daily knowledge from the sociocultural context of students. To achieve this objective, a study was carried out primarily, a study referring to the three central points of this project, Mathematical Modeling, Countryside Education and Significant Learning Theory, in order to support subsequent activities.Then, a mapping was made on digital platforms, in search of publications that contemplated the themes discussed in the theoretical framework. After this stage, three investigative activities were elaborated and applied, they are: a) questionnaire for the investigation of the subsunçores; b) rain of ideas about the "Mathematics of the Field" and c) observation of the daily school. Thus, the activities were developed with a group of elementary school students from a school in the field in order to evaluate the subsunçores and the elements of the context of the field that were most present in the school community, in order to list subsidies for the construction of potentially significant teaching activities.After analyzing the results of the first interventions, a sequence of activities based on three major themes a) Livestock; (b) Fishing and (c) agriculture. Thus, from contextualizations, as they value the stages of Mathematical Modeling, we went to the field to investigate whether through contextualizations and other stages of the methodology, it was possible to provide a significant learning of mathematical content, since the approaches involved concepts already studied and the construction of new concepts. The results obtained after application revealed that activities involving knowledge from cultural aspects arouse greater interest from the subjects, which can be observed during the application, since through the collective and collaboration of the subjects students was possible to build new mathematical knowledge and also the reinforcement of knowledge already worked on other classroom opportunities.Thus, we understand that meaningful learning occurred when, when presenting a common situation of their routine in the form of a problem, the subjects had to learn to think, without the concern of presenting visible results, mobilizing thus affective, cognitive and cultural aspects in a mutual way, which resulted in a higher performance and occasioned dialogues throughout the process, understanding this as a collaborative construction. We also point out that for Ausubel (2003) it is important that activities that are elaborated in order to provide students with meaningful learning should contemplate novelty, since when faced with this situation are exposed to participate effectively, to discuss, to think and question their own experience, factors that are intrinsic to the human being.